Youth Participation With Local Councils: a Snapshot of Office Reflections Involving Young People in Decision-Making - Peteru, Paul Seilala (Auckland University of Technology, 2006)
The study incorporates work carried out by the Auckland Regional Child and Youth Engagement Project (ARCYE). The ARCYE project is part of the Auckland Sustainable Cities, 'Investing in Child and Youth Development' (ICYD) work strand which began in 2003 and was completed in June 2006. The researcher interviewed officers of the seven cities and district councils in the Auckland region and the Auckland Regional Council, all of whom had a child and youth focus within their organisation. The interviews examined the drivers for youth participation from a local government perspective. They shared their experiences in engaging youth to participate in Council sponsored or supported initiatives. The objective was to find out what the benefits of youth participation were for Councils and also for the participating youth. The research supports the proposition that for the Auckland region's economic growth to be sustainable, the next generation of leaders, skilled workers, entrepreneurs, educators and parents must be critically involved in today's discourse concerning the region's development. Therein is the rationale for local government to engage young people. The research posits that the 'whole of government' (central government and local government with community) focus on investing in child and youth development is not random. Rather it is a strategic effort to prepare young people to become responsive to their region's growth and development. The downstream benefits may see engaged youth as a captive audience being open to influence from adults. The value or benefit of including young people in decision-making opportunities therefore needs to be carefully considered within a context of young people's apparent diminished status within society. Youth participation with local councils needs to be real: Young people participating and contributing to the improvement of their communities. As a corollary youth rights within an adult-controlled and managed society requires careful monitoring to minimise the exploitation of young people by adults.
Keywords: Local government; Auckland Region; Citizen participation; Maori Development